Short-Term Efficacy of High-Intensity Laser Therapy in Alleviating Pain in Patients with Knee Osteoarthritis: A Single-Blind Randomised Controlled Trial - Punpetch Siriratna; Chompoonuch Ratanasutiranont; Thongsuk Manissorn; Nonthalee Santiniyom; Waree Chira-Adisai (Pain Research and Management)
Objectives. The aim of the study is to evaluate the efficacy of high-intensity laser therapy (HILT) on pain reduction in patients with knee osteoarthritis (OA). Methods. Forty-two patients diagnosed with primary knee OA, with a Kellgren–Lawrence classification of 2–4, were recruited into the study. The patients were randomly allocated to two groups: HILT and control. The intervention group received HILT (energy density of 22.39 J/cm2, 562.5 joule/session), while the control group received a sham laser, which was done 2–3 sessions per week for a total of 10 sessions. Both the groups also received the same conservative treatment. The main outcome measures were the visual analogue scale (VAS) and the modified Thai version of the Western Ontario and McMaster Universities Osteoarthritis Index (T-WOMAC) which were evaluated at baseline and immediately after treatment completion. Results. At the end of the study, the overall analysis showed a significant decrease in VAS and T-WOMAC scores in both the groups; a greater decrease in scores was found in the HILT group than in the control group (p<0.001). The between-group comparison also showed a significant difference in VAS, but not in the T-WOMAC score, favouring HILT (p<0.05). Conclusion. The HILT plus conservative treatment can help alleviate pain in patients with knee OA. The findings of the present study could be used in clinical practice to add HILT as another noninvasive treatment option for knee OA. This could be advantageous, particularly for individuals who are at high risk of surgery due to multiple comorbidities or older people. Trial Registration. This clinical trial registration was performed at Clinical.gov (NCT04889885).